Correlation between lactate/albumin ratio and 28-day mortality in sepsis-associated acute kidney injury patients - Susu He; Yongkang Wang; Shiyu Wei; Shifeng Yang (Frontiers in Medicine)
BackgroundThe lactate/albumin ratio (LAR) was related to adverse outcomes in heart failure, myocardial infarction, and acute pancreatitis. However, it remains unevaluated whether LAR has prognosis significance in sepsis-associated acute kidney injury (SA-AKI) patients. Therefore, this research was performed to clarify the potential predictive utility of LAR for 28-day mortality in SA-AKI patients.MethodsParticipants diagnosed with SA-AKI were selected from the Medical Information Mart for Intensive Care (MIMIC-IV) database and then placed into four groups in accordance with LAR quartiles. The endpoint was all-cause mortality within 28 days. The Kaplan–Meier curves were conducted to estimate the cumulative survival rates in the four groups. The correlation between LAR and the endpoint was elucidated by constructing Cox proportional hazards analysis, restricted cubic splines (RCS), and subgroup analysis.ResultsOf the 3,895 patients with SA-AKI, 58.59% were men. The mortality rate from all causes within 28 days was 28.55%. The Kaplan–Meier curves showed that participants having elevated LAR exhibited significantly decreased survival rates. Cox proportional hazards models showed that higher LAR was related to higher 28-day death rate in SA-AKI patients (HR: 1.224, 95% CI: 1.160–1.291, p < 0.001). In addition, RCS analyses revealed that LAR was non-linearly correlated with the risk of 28-day death.ConclusionLAR was independently related to an elevated risk of mortality within 28 days in SA-AKI patients. More prospective research studies are necessitated for further confirmation of these findings.